GRACE observes small?scale mass loss in Greenland - Wouters, B. (author); Chambers, D. (author); Schrama, E.J.O. (author) (Geophysical Research Letters, 2008)
Using satellite gravity data between February 2003 and January 2008, we examine changes in Greenland's mass distribution on a regional scale. During this period, Greenland lost mass at a mean rate of 179 ± 25 Gt/yr, equivalent to a global mean sea level change of 0.5 ± 0.1 mm/yr. Rates increase over time, suggesting an acceleration of the mass loss, driven by mass loss during summer. The largest mass losses occurred along the southeastern and northwestern coast in the summers of 2005 and 2007, when the ice sheet lost 279 Gt and 328 Gt of ice respectively within 2 months. In 2007, a strong mass loss is observed during summer at elevations above 2000 m, for the first time since the start of the observations. Space Engineering Aerospace Engineering